Evaluation of engineering properties of clayey sand bio-mediated with terrazyme enzyme - Nadeem, Muhammad; Ullah, Sami; Chen, Shanxiong; Alkahtani, Meshel Q.; Khan, Mohammad Arsalan; Salih, Rania; Jian, Li; Mursaleen, Mohammad; Islam, Saiful; Ahmad, Jamal (Frontiers in Materials, 2023)
Soil stabilization is a practical approach for enhancing the suitability of problematic soil in construction projects. This study focusses on analyzing the impact of the bio-enzyme Terrazyme on the engineering properties of Mirpur soil, which exhibits inadequate performance as subgrade soil, particularly in moist conditions. The study investigates key engineering characteristics, including unconfined compressive strength (UCS), California Bearing Ratio (CBR), maximum dry density (MDD), Atterberg's Limits, and compressibility index. Additionally, X-Ray Diffraction and SEM analysis were conducted to identify the mineral composition and particle structure of Mirpur soil. The findings will contribute to a better understanding of the efficacy of bio-mediated soil stabilization techniques.